Determination of Phenolics and Flavonoids of Some Useful Medicinal Plants and Bioassay-Guided Fractionation Substances of Sclerocarya birrea (A. Rich) Hochst Stem (Bark) Extract and Their Efficacy Against Salmonella typhi - Abdallah, Muhammad Salihu; Mustafa, Muskhazli; Nallappan, Meenakshii A/P.; Choi, Sangho; Paik, Jin-Hyub; Rusea, Go (Frontiers in Chemistry, 2021)
Gallic acid and Catechin were the most abundant phenolics and Flavonoids contents mostly found in all plants extracts. Contents and the bioassay guided fractionating substances on S. birrea fraction played vital role. The goal of the study is to determine the contents of some useful medicinal plants and the bioassay guided fractionating substances on S. birrea fraction compounds capable of actions against the isolate using LC-MS. Folin-Ciocalteu’s reagent procedure followed by flavonoid content determination were measured spectrophotometrically. The bioassay-guided fractionation, chronological partition and later screened the antibacterial action against Salmonella typhi. Nevertheless, ethyl acetate fraction extracts of S. birrea stem (bark) extract was analysed using (LC-HRMS). Moreover, Gallic acid increased tremendously in Vachellia nilotica pods extracts with a curve (R2 = 0.9958).While large Catechin increase noticed in Sclerocarya birrea stem (bark) extracts followed by V. nilotica pods extracts with a curve (R2 = 0.9993), were all significantly different at P-value < 0.0001. Subsequently, 10mg/ml of S. birrea stem (bark) ethyl acetate fraction extract was the MIC where by no MBC recorded and susceptible to the positive control being highest inhibition zone followed by ethyl acetate fraction extract at 10mg/ml (9.7±0.0) at P<0.0001 turkey. The Vidarabine happened to be the Nobel compound found in the S. birrea stem (bark), reasonable amount of phenolics and flavonoids contents determined the actions of individual plants.